Pengembangan Paket Wisata Kebugaran Berbasis Stingless Bee Honey: Analisis Komponen 4A pada Gudem Bee Farm, Bintan - Putri Fistyaning Army; Natasha Herawati (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
The growing trend of wellness tourism is driving increasing tourist demand for activities that support physical, mental, and emotional health. This study aims to develop a wellness tourism package based on education about stingless bee honey at Gudem Bee Farm as an effort to diversify local tourism products. Data were obtained through field observations of tourist facilities and activities, interviews with Gudem Bee Farm managers regarding the potential and needs for package development, and documentation in the form of photos, destination profiles, and other supporting data. The package planning was compiled by analyzing the 4A components (Attraction, Accessibility, Amenities, Ancillary Services). The results show that the main activities integrated into the package include tasting honey from the hive, making and using a natural mask made from stingless bee honey, nature bonding, mindful eating, and mindful drinking of wedang telang (blue telang tea). Accessibility and supporting facilities were deemed adequate, although there were obstacles such as changes in operational costs, limited field data, diverse tourist preferences, and potential weather disturbances. This planning resulted in a daily wellness tourism package design that is feasible to implement and has the potential to increase the attractiveness of Gudem Bee Farm through sustainable utilization of local potential.